Vitamin D Treatment Sequence Is Critical for Transcriptome Modulation of Immune Challenged Primary Human Cells - Malmberg, Henna-Riikka; Hanel, Andrea; Taipale, Mari; Heikkinen, Sami; Carlberg, Carsten (Frontiers in Immunology, 2021)
Microbe-associated molecular patterns, such as lipopolysaccharide (LPS) and -glucan (BG), are surrogates of immune challenges like bacterial and fungal infections, respectively. The biologically active form of vitamin D, 1α,25-dihydroxyvitamin D3 (1,25(OH)2D3), supports the immune system in its fight against infections. This study investigated significant and prominent changes of the transcriptome of human peripheral blood mononuclear cells that immediately after isolation are exposed to 1,25(OH)2D3-modulated immune challenges over a time frame of 24-48 h. In this in vitro study design, most LPS and BG responsive genes are downregulated and their counts are drastically reduced when cells are treated 24 h after, 24 h before or in parallel with 1,25(OH)2D3. Interestingly, only a 1,25(OH)2D3 pre-treatment of the LPS challenge results in a majority of upregulated genes. Both immune challenges display characteristic differences in responsive genes and their associated pathways, to which the actions of 1,25(OH)2D3 often oppose. The joined BG/1,25(OH)2D3 response is less sensitive to treatment sequence than that of LPS/1,25(OH)2D3. In conclusion, the functional consequences of immune challenges are significantly modulated by 1,25(OH)2D3 but largely depend on treatment sequence. This may suggest that a sufficient vitamin D status before an infection is more important than vitamin D supplementation afterwards.